2016
DOI: 10.1002/admi.201600128
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Superoleophobicity of Cotton Fabrics for Efficient Oil–Water Separation

Abstract: dispersal oil using chemical dispersants, in situ burning, and so on. [4][5][6][7][8] The option for oil collection using filtration was considered as an attractive choice because of its simplicity for the proper disposal of free and dispersed oil in water body.In the last decade, textile materials have gained much attention as membranes or sorbents for oil-water separation due to their high flexibility, moderate absorption capability, low density, reasonable price, and excellent biocompatibility. Typically, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…Fabrics treated with 0.1% and 0.3% Si-HNT particle concentration show that much of the cotton fiber surface is bare and does not contain many Si-HNT particles, while fabric treated with 0.5% Si-HNT particle concentration shows most of cotton fiber surface covered with particles. [5] The tensile data presented in Figure 8a While the results of an earlier study had indicated that the fatty acid grafting on cotton fabrics using microwave causes 47% and 50% strength loss in the warp and weft directions, respectively, due to the high temperature caused by microwave treatment, no such strength loss was found in this study. Whereas fabric treated with pure HNT particles and fatty anhydride results in ultrahydrophobic fabric at first, but the water drop gets absorbed in just a few seconds.…”
Section: Characterization Of Treated Fabricscontrasting
confidence: 61%
See 1 more Smart Citation
“…Fabrics treated with 0.1% and 0.3% Si-HNT particle concentration show that much of the cotton fiber surface is bare and does not contain many Si-HNT particles, while fabric treated with 0.5% Si-HNT particle concentration shows most of cotton fiber surface covered with particles. [5] The tensile data presented in Figure 8a While the results of an earlier study had indicated that the fatty acid grafting on cotton fabrics using microwave causes 47% and 50% strength loss in the warp and weft directions, respectively, due to the high temperature caused by microwave treatment, no such strength loss was found in this study. Whereas fabric treated with pure HNT particles and fatty anhydride results in ultrahydrophobic fabric at first, but the water drop gets absorbed in just a few seconds.…”
Section: Characterization Of Treated Fabricscontrasting
confidence: 61%
“…[5][6][7] Ultrahydrophobic surfaces found in nature such as lotus leaves, cicada wings, and many others show a unique combination of the hierarchical rough structure with a hydrophobic waxy layer present on the surface. Some of the other applications of ultrahydrophobic cellulose include anti-biofouling, separating oil from water for cleaning oil spills in offshore oil fields or tanker vessels, cellulose films used in packaging, and improving interfacial bonding of cellulosic fibers or micro and nanofibrils for use in nonpolar resins for fabricating fiber reinforced composites or simply obtaining high strength resins.…”
Section: Direct Assembly Of Silica Nanospheres On Halloysite Nanotubementioning
confidence: 99%
“…The BMCM showed an average mean square roughness (Ra) of 25.952 nm, which is much higher than that of stainless steel mesh (17.486 nm) within the same area scanned. This is due to the existence of dendritic structures on the BMCM surface, which could increase the surface roughness and hierarchy . Chemical composition analysis of BMCM was carried out using EDS and XRD.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the existence of dendritic structures on the BMCM surface, which could increase the surface roughness and hierarchy. [42,43] Chemical composition analysis of BMCM was carried out using EDS and XRD. Figure 7e www.small-journal.com solution and SNWF was modified by stearic acid successfully.…”
Section: Resultsmentioning
confidence: 99%
“…[13] The second type is films with superhydrophilicity/underwater superoleophobicity,s uch as hydrogel-coated metal films, [33] porousn itrocellulose membranes, [34] and Cu(OH) 2 -coated copperm esh films, [35] that can separate water from the mixture. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Notably,a ll these films can only separatec ertain types of oil/water mixture, either light oil/water mixtures (1 oil < 1 water )o rh eavy oil/water mixtures (1 oil > 1 water ). Briefly,i ns uperhydrophobic/superoleophilic films that can removeo il from mixtures, light oil/water mixtures (1 oil < 1 water )a re unfavorable because the water can sink down and accumulate on the film as ab arrier layer,w hich thusb locks oil permeation.…”
Section: Introductionmentioning
confidence: 99%